Cohort differences in attitudes toward sexual orientation: the formative political climate as a socializing agent - Jeannet, Anne-Marie; Dražanová, Lenka (Frontiers in Political Science, 2023)
Introduction Why do cohorts differ in their attitudes toward sexual orientation and what is the role of societal values during formative years? We investigate whether discontinuities in the prevailing values of equality and tradition in a person's formative years impinge on their attitudes toward sexual orientation as adults. Methods We test this by integrating historical political data from the Manifesto Project Dataset with contemporary micro-data on attitudes toward sexual orientation from 10 rounds of the European Social Survey (2002-2020) across 13 cohorts in 13 European countries. Results and discussion Using hierarchical age-period-cohort analysis with synthetic age cohorts, we find if the value of equality is politically diffuse, it can have a socializing effect. We find that the individuals who came of age during a period when political values of equality were more dominant are more tolerant of gays and lesbians. On the other hand, we do not find any evidence that individuals who experience youth during a time of more traditional political values have more negative opinions about different sexual orientations. Overall, these findings suggest that cohorts adopt distinct patterns of attitudes toward gays and lesbians as a result of a collective process of socialization during their impressionable years.